Natural disease escapes as sources of resistance against cardamom mosaic virus causing katte disease of cardamom (Elettaria cardamomum Maton) - VENUGOPAL, M N (Journal of Spices and Aromatic Crops, 1999)
Resistant sources to cardamom mosaic virus causing katte disease of cardamom (Elettaria cardamomum) were identified by collecting 134 disease escapes from hot spots of virus infection in South India and screening them in greenhouse, sick plot and hot spots. Testing of promising collections in four hot spots and also against natural infection confirmed the resistant nature of the collections.